Cabergoline in severe ectopic or occult Cushing's syndrome. Issue 1 (July 2019) - Ilie, Mirela Diana; Raverot, Véronique; Tronc, François; Vasiljevic, Alexandre; Borson-Chazot, Françoise; Raverot, Gérald
Abstract : Context: Cabergoline has been shown to have some effect in the treatment of moderate Cushing's disease, but its effectiveness in Cushing's syndrome of ectopic or occult origin remains to be investigated. Case series: In this case series, cabergoline was used in combination with steroidogenesis inhibitors in nine patients with severe Cushing's syndrome of ectopic or occult origin. Cabergoline's effectiveness enabled rapid withdrawal of the steroidogenesis inhibitors and long-term control of the hypercortisolism in three of the cases. Review of the literature: In the literature, we found only 11 cases of ectopic or occult Cushing's syndrome treated with dopamine receptor agonists, alone or in combination. Yet of these 11 cases, 10 responded. Conclusions: Although limited, the existing experience highlights the potential value of cabergoline in the treatment of ectopic or occult Cushing's syndrome.